2023
DOI: 10.1371/journal.pone.0282435
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the properties of ultra-high-strength geopolymer concrete with polypropylene fibers and nano-silica

Abstract: Because of the recent progress in materials properties, specifically high-strength concrete, further research is needed to evaluate its suitability, understanding, and performance in the modern-day world. This research aims to enhance the performance of ultra-high-strength geopolymer concrete (UHS-GPC) by adding nano-silica (NS) and polypropylene fibers (PPFs). Three 1%, 2%, and 3% different amounts of PPFs and three NS 5%, 10%, and 15% were utilized in the samples. Various performance parameters of UHS-GPC we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…This phenomenon may potentially result from the influence of these mineral filler materials, which exert a noteworthy impact on the rheological characteristics. Althoey et al [ 16 ] revealed that adding Nano-silica significantly affected the flow diameter of UHPGPC. The authors observed that UHSGPC with 10 % Nano-silica (see Fig.…”
Section: Fresh Characteristics Of Uhpgpcmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon may potentially result from the influence of these mineral filler materials, which exert a noteworthy impact on the rheological characteristics. Althoey et al [ 16 ] revealed that adding Nano-silica significantly affected the flow diameter of UHPGPC. The authors observed that UHSGPC with 10 % Nano-silica (see Fig.…”
Section: Fresh Characteristics Of Uhpgpcmentioning
confidence: 99%
“…Notably, literature studies [ 40 , 82 ] employed polyethylene and polyvinyl alcohol as primary fiber constituents, observing significant enhancements in load-bearing capacity, energy absorption, and fracture energy up to 70-fold increases in specimens containing these fibers. Althoey et al [ 16 ] evaluated the impact of different percentages of Nano-silica (5 %, 10 %, and 15 %) and PPFs (1 %, 2 %, and 3 %) on the flexural and load-deflection behavior of ultra-high strength geopolymer concrete. The authors observed that the flexural strength experienced an increase from 22.7 MPa to 25.43 MPa (see Fig.…”
Section: Strength Characteristics Of Uhpgpcmentioning
confidence: 99%
See 1 more Smart Citation
“…The fresh property was reported to get worse with the addition of 20% to 30% silica fume, which revealed that the silica fume significantly affects the fresh and strength properties of geopolymer concrete at a high replacement percentage. Althoey et al [ 41 ] developed ultra-high-strength fiber-reinforced geopolymer concrete by substituting cement with nano-silica and activated with the alkaline activators and observed significant results.…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymer concrete (GC) is a sustainable [9,10], eco-friendly construction material that has garnered significant attention in recent years due to its exceptional mechanical properties and durability [11][12][13][14][15]. GC is made from an alkali-activated binder system consisting of industrial by-products such as fly ash and metakaolin, significantly reducing cement production's environmental impact [16,17].…”
Section: Introductionmentioning
confidence: 99%